Functions and regulatory framework of ZmNST3 in maize under lodging and drought stress. (23rd July 2020) - Ren, Zhenzhen; Zhang, Dongling; Cao, Liru; Zhang, Weiqiang; Zheng, Hongjian; Liu, Zhixue; Han, Shengbo; Dong, Yahui; Zhu, Fangfang; Liu, Huafeng; Su, Huihui; Chen, Yanhui; et al.
Abstract: The growth and development of maize are negatively affected by various abiotic stresses including drought, high salinity, extreme temperature, and strong wind. Therefore, it is important to understand the molecular mechanisms underlying abiotic stress resistance in maize. In the present work, we identified that a novel NAC transcriptional factor, ZmNST3, enhances maize lodging resistance and drought stress tolerance. ChIP‐Seq and expression of target genes analysis showed that ZmNST3 could directly regulate the expression of genes related to cell wall biosynthesis which could subsequently enhance lodging resistance. Furthermore, we also demonstrated that ZmNST3 affected the expression of genes related to the synthesis of antioxidant enzyme secondary metabolites that could enhance drought resistance. More importantly, we are the first to report that ZmNST3 directly binds to the promoters of CESA5 and Dynamin‐Related Proteins2A ( DRP2A ) and activates the expression of genes related to secondary cell wall cellulose biosynthesis. Additionally, we revealed that ZmNST3 directly binds to the promoters of GST/GlnRS and activates genes which could enhance the production of antioxidant enzymes in vivo. Overall, our work contributes to a comprehensive understanding of the regulatory network of ZmNST3 in regulating maize lodging and drought stress resistance. Abstract : The growth and development of maize are negatively affected by drought and strong wind. Therefore, it is important to understand the molecular mechanisms underlying abiotic stress resistance in maize. We showed that ZmNST3 positively regulates the resistance in lodging and drought stress, and improve maize lodging resistance by directly regulating various genes related to cell wall biosynthesis (e.g., CESA5, DRP2A ). Moreover, ZmNST3 could enhance drought tolerance by regulating genes related to the antioxidant enzyme system, cell wall biosynthesis and other pathways. Our findings elucidate the underlying mechanisms for the development of lodging‐resistant and drought‐tolerant germplasm.